Relationship Between the Nurse Educators Role and Nutrition Intake in Chemotherapy Patients Who Have Nausea - Joko Susilo, Eko; Ira Handian, Feriana; Dafir Firdaus, Achmad (Devotion : Journal of Research and Community Service, 2022)
Nausea is one of the effects of chemotherapy that can interfere with nutritional intake so that it interferes with the ongoing chemotherapy program. Lack of nutritional intake due to nausea can be prevented by educating chemotherapy patients in reducing nausea. Nurses carry out their role as educators in an effort to improve health through behavior that supports health, one of which is educators. This study aims to determine the relationship between the role of nurses and educators with nutritional intake in chemotherapy patients who experience nausea at IRNA II RSUD Dr. Saiful Anwar Malang. This type of research is an analytical survey using a crisis sectional approach. The population of this study was chemo patients who were nauseous within 1 month with the number of patients per month ± 32 people. Data were taken on average for patients from January to May 2021 and carried out in September. The sampling technique in this study was non-probability sampling with purposive sampling technique. The research instrument was a nurse educator role questionnaire consisting of 30 questions and a nutrition intake questionnaire filled out 24 hours in the morning, afternoon and evening. The results of the Spearman correlation test showed a correlation value (r) of 0.463 (46.3%) and a p-value of 0.01. The value of p<α (00.5), which means that there is a relationship between the role of nurses as educators with nutritional intake in chemotherapy patients who experience nausea in IRNA II RSUD Dr. Saiful Anwar Malang.